2005
DOI: 10.1197/j.aem.2005.03.525
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Community‐based Public Access Defibrillation in the PAD Trial

Abstract: Background: The Public Access Defibrillation (PAD) Trial was a randomized, controlled trial designed to measure survival to hospital discharge following out-of-hospital cardiac arrest (OOH-CA) in community facilities trained and equipped to provide PAD, compared with community facilities trained to provide cardiopulmonary resuscitation (CPR) without any capacity for defibrillation. Objectives: To report the implementation of community-based lay responder emergency response programs in 1,260 participating facil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…(7,8) That is why, in most countries of the world there is an awareness about use of public automatic external defibrillators (PAED), that has increased the survival of patients with cardiac arrest. (9) There are public facilities, residential and commercials buildings that have this equipment, 13% of working places and 11.6% of public facilities, commercial and residential buildings have used PAED d at least once in the last year. (10) To make a 10 years forecast, it is estimated that between 90 to 100% of public facilities might use the equipment at least once.…”
Section: Discussionmentioning
confidence: 99%
“…(7,8) That is why, in most countries of the world there is an awareness about use of public automatic external defibrillators (PAED), that has increased the survival of patients with cardiac arrest. (9) There are public facilities, residential and commercials buildings that have this equipment, 13% of working places and 11.6% of public facilities, commercial and residential buildings have used PAED d at least once in the last year. (10) To make a 10 years forecast, it is estimated that between 90 to 100% of public facilities might use the equipment at least once.…”
Section: Discussionmentioning
confidence: 99%
“…A purposive sampling strategy was used to identify and recruit focus-group participants who were representative of the NYC PAD buildings' population with respect to age, gender, and race/ethnicity. 12,13 Because 20% of the PAD units reported a large number of Spanish speakers, two of the six focus groups were conducted in Spanish. Building staff members who had served as liaisons for the PAD Trial identified interested prospective participants; phone calls were then made by Community VOICES Study staff inviting the prospective participants to the focus groups.…”
Section: Methodsmentioning
confidence: 99%
“…Participating buildings were required to meet eligibility criteria regarding expected frequency of cardiac arrest; thus, the sites had a large number of persons more than 50 years of age. 9,12 At each location, volunteers were trained to recognize and treat cardiac arrest, and a system was implemented to summon one of these trained individuals (referred to as ''lay responders'') whenever a cardiac arrest occurred on the premises. 13 In half of the buildings, the lay responders were trained in cardiopulmonary resuscitation (CPR) only; in the other half, they were also trained to use AEDs.…”
mentioning
confidence: 99%
“…To improve survival after OHCA, the AHA and its affiliates have developed community programs to raise public awareness of the signs of cardiac arrest and the importance of bystander CPR. [42][43][44] However, even trained bystanders sometimes encounter intellectual and volitional barriers when it comes to performing CPR. The traditional strategy has been to train as many community members as possible.…”
Section: Communitymentioning
confidence: 99%